2014
DOI: 10.1371/journal.pone.0102176
|View full text |Cite
|
Sign up to set email alerts
|

The Three Receptor Tyrosine Kinases c-KIT, VEGFR2 and PDGFRα, Closely Spaced at 4q12, Show Increased Protein Expression in Triple-Negative Breast Cancer

Abstract: BackgroundTriple-negative breast cancer (TNBC) is a heterogeneous subgroup of breast cancer with poor prognosis and no targeted therapy available. Receptor tyrosine kinases (RTKs) are emerging targets in anticancer therapy and many RTK-inhibiting drugs are currently being developed. The aim of this study was to elucidate if there is a correlation between the protein expression of three RTKs c-KIT, VEGFR2 and PDGFRα, their gene copy number, and prognosis in TNBC compared to non-TNBC.MethodsTumor tissue samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 44 publications
(63 reference statements)
2
36
0
3
Order By: Relevance
“…Nuclear staining in >1% of tumor cell nuclei was considered a positive indication of the presence of ER and PR. Immunostaining for HER2 and CD117 ( 11 , 21 ) was graded according to the percentage of cells: 0, none; 1+, <10% staining weak and incomplete; 2+, ≥10%, staining weak to moderate; and 3+, ≥10% strong staining. HER2 immunostaining was considered positive if graded 3+, or if gene amplification was confirmed by fluorescence in situ hybridization (FISH) in patients exhibiting 2+ immunostaining.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear staining in >1% of tumor cell nuclei was considered a positive indication of the presence of ER and PR. Immunostaining for HER2 and CD117 ( 11 , 21 ) was graded according to the percentage of cells: 0, none; 1+, <10% staining weak and incomplete; 2+, ≥10%, staining weak to moderate; and 3+, ≥10% strong staining. HER2 immunostaining was considered positive if graded 3+, or if gene amplification was confirmed by fluorescence in situ hybridization (FISH) in patients exhibiting 2+ immunostaining.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining has revealed that CD117 protein is overexpressed in primary malignant tumors, including operable esophageal squamous cell carcinoma and vulvar melanoma, and may be a valuable prognostic marker in esophageal squamous cell carcinoma ( 8 ). However, the results of studies concerning the prognostic significance of CD117 in patients with breast cancer or TNBC are conflicting: Kashiwagi et al have suggested that CD117 protein is associated with poor prognosis ( 9 ), whereas others identified no significant association between CD117 and prognosis in breast cancer or TNBC ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…c-Kit may be expressed in ~25%–45% of TNBC, 64 , 65 but studies disagree as to whether c-Kit levels predict the overall survival of TNBC patients. 10 , 66 , 67 A Phase II trial examined sunitinib (a targeted agent that inhibits c-Kit as well as multiple other kinases) as monotherapy in patients with advanced TNBC as compared to standard chemotherapeutic regimen and found that sunitinib was not an effective treatment. 68 Because of the controversial evidence of c-Kit in TNBC, more studies are needed in order to determine its potential usefulness as a TNBC biomarker.…”
Section: Tnbc Biomarkers On the Cell Surface Membranementioning
confidence: 99%
“…OneofpotentialmarkersisCD117,atransmembraneproteinthatreceivesthemessagefromastemcell factor (SCF). CD117 protein is encoded by the proto-oncogene c-kit and belongs to the tyrosine kinasereceptorfamily [20,21].Recentstudieshave suggestedthatCD117proteinisaberrantlyregulatedinmalignanciesofthesalivarygland [22],retinoblastoma [23],endometrium [24],papillarythyroid [25],andbreast [26].CD117isalsoanauthoritative protein in the diagnosis of gastrointestinal stromal tumours (GIST), where it generally shows positive expression [27].Severalstudiesthatconcentratedon CD117 protein in lung cancer showed that CD117 proteinexpressionhadnoeffectonprogressionand prognosisoflungcarcinoma [20,28],whereasother studies have suggested that CD117 protein could beusedasabiomarkerforlungcarcinoma [29,30,31].Thepurposeofthepresentcomprehensivemeta-analysis was to clarify the relationship between CD117proteinandlungcarcinoma.…”
Section: Introductionmentioning
confidence: 99%